Direct Evidence for Using Coriandrum sativum var. microcarpum Essential Oil to Ameliorate Scopolamine-Induced Memory Impairment and Brain Oxidative Stress in the Zebrafish Model - Ion Brinza; Razvan Stefan Boiangiu; Oana Cioanca; Monica Hancianu; Gabriela Dumitru; Lucian Hritcu; Gheorghe-Ciprian Birsan; Elena Todirascu-Ciornea (MDPI AG, 2023)
Essential oil from Coriandrum sativum has been demonstrated to provide various pharmacological properties, such as antioxidant, antimicrobial, antibacterial, antifungal, antidiabetic, anticonvulsive, anxiolytic-antidepressant, and anti-aging properties. This study investigated the mechanism of Coriandrum sativum var. microcarpum essential oil (CSEO, 25, 150, and 300 μL/L) and cognitive impairment and brain oxidative stress in a scopolamine (SCOP, 100 μM) zebrafish model (Danio rerio) of cognitive impairment. Spatial memory, response to novelty, and recognition memory were assessed using the Y-maze test and the novel object recognition test (NOR), while anxiety-like behavior was investigated using the novel tank diving test (NTT). The cholinergic system activity and brain oxidative stress were also evaluated. CSEO was administered to zebrafish once a day for 21 days, while SCOP and galantamine (GAL, 1 mg/L) were delivered 30 min before behavioral testing and euthanasia. Our data revealed that SCOP induced memory dysfunction and anxiety-like behavior, while CSEO improved memory performance, as evidenced by behavioral tasks. Moreover, CSEO attenuated SCOP-induced brain oxidative stress and decreased acetylcholinesterase (AChE) activity. The results demonstrated the potential use of the CSEO in providing beneficial effects by reducing memory deficits and brain oxidative stress involved in the genesis of a dementia state.